Increased RNA Transcription of Energy Source Transporters in Circulating White Blood Cells of Aged Mice - Takeuchi, Yukiko; Saino, Orie; Okinaka, Yuka; Ogawa, Yuko; Akamatsu, Rie; Kikuchi-Taura, Akie; Kataoka, Yosky; Maeda, Mitsuyo; Gul, Sheraz; Claussen, Carsten; Boltze, Johannes; Taguchi, Akihiko (Frontiers in Aging Neuroscience, 2022)
Circulating white blood cells (WBC) contribute towards maintenance of cerebral metabolism and brain function. Recently, we showed that during ageing, transcription of metabolism related genes, including energy source transports, in brain significantly decreased at the hippocampus resulting in impaired neurological functions. In this article, we investigated the changes in RNA transcription of metabolism related genes (glucose transporter 1 [Glut1], Glut3, monocarboxylate transporter 4 [MCT4], hypoxia inducible factor 1-α [Hif1-α], prolyl hydroxylase 3 [PHD3] and pyruvate dehydrogenase kinase 1 [PDK1]) in circulating WBC and correlated these with brain function in mice. Contrary to our expectations, most of these metabolism related genes in circulating WBC significantly increased in aged mice, and correlation between their increased RNA transcription and impaired neurological functions was observed. Bone marrow mononuclear transplantation into aged mice decreased metabolism related genes in WBC with accelerated neurogenesis in hippocampus. In vitro analysis revealed that cell-cell interaction between WBC and endothelial cells via gap junction is impaired with aging, and blockade of the interaction increased their transcription in WBC. Our findings indicate that gross analysis of RNA transcription of metabolism related genes in circulating WBC has the potential to provide significant information relating to impaired cell-cell interaction between WBC and endothelial cells of aged mice. Additionally, this can serve as a tool to evaluate the change of the cell-cell interaction caused by various treatments or diseases.